Hydrodynamic fluctuations in fluids and fluid mixtures - Ortiz de Zarate, Jose M. (Elsevier, 2006)
This book deals with density, temperature, velocity and concentration fluctuations in fluids and fluid mixtures. The book first reviews thermal fluctuations in equilibrium fluids on the basis of fluctuating hydrodynamics. It then shows how the method of fluctuating hydrodynamics can be extended to deal with hydrodynamic fluctuations when the system is in a stationary nonequilibrium state. In contrast to equilibrium fluids where the fluctuations are generally short ranged unless the system is close to a critical point, fluctuations in nonequilibrium fluids are always long-ranged encompassing the entire system. The book provides the first comprehensive treatment of fluctuations in fluids and fluid mixtures brought out of equilibrium by the imposition of a temperature and concentration gradient but that are still in a macroscopically quiescent state. By incorporating appropriate boundary conditions in the case of fluid layers, it is shown how fluctuating hydrodynamics affects the fluctuations close to the onset of convection. Experimental techniques of light scattering and shadowgraphy for measuring nonequilibrium fluctuations are elucidated and the experimental results thus far reported in the literature are reviewed. Systematic exposition of fluctuating hydrodynamics and its applications First book on nonequilibrium fluctuations in fluids Fluctuating Boussinesq equations and nonequilibrium fluids Fluid layers and onset of convection Rayleigh scattering and Brillouin scattering in fluids Shadowgraph technique for measuring fluctuations Fluctuations near hydrodynamic instabilities.